Ecological correlation between aquatic vegetation and freshwater fish populations in Perak River, Malaysia - SITI NORASIKIN ISMAIL; MUZZALIFAH ABD HAMID; MASHHOR MANSOR (Society for Indonesian Biodiversity, 2018)
Ismail SN, Abd Hamid M, Mansor M. 2018. Ecology, diversity and seasonal distribution of wild mushrooms in a Nigerian tropical forest reserve. Biodiversitas 19: 279-284. Aquatic plants play a crucial role in an aquatic ecosystem partly because these plant communities provide suitable habitats and food items to other aquatic organisms especially fish. Many fish communities use vegetation as breeding sites, nurseries and refuges for their juveniles. Therefore, this study was conducted to provide baseline data on the correlation between the aquatic plants and freshwater fishes in Perak River. Based on the findings, the abundance of aquatic plant influences the growth and health of the fish. Habitats with moderate amounts of aquatic vegetation provide the optimal environment for many fish and hence, increase the fish diversity, feeding, growth, and reproduction. In contrast, both limited and excessive vegetation may decrease fish growth rates at 75% to 85% of plant community coverage. The recent trip along the Perak discloses the presence of these aquatic plants at certain habitats. There is a positive correlation between aquatic plants and freshwater fish. The association between aquatic plants and fish assemblages has been documented in scientific studies with the conclusion that moderate plant densities could enhance the fish diversity, feeding, growth, and reproduction.